Anticipation and decision making in sport - Williams, A. M. 1965-; Jackson., Robin C. (Routledge, 2019)
"Anticipation and Decision-Making in Sport is the first book to identify the underlying science behind anticipation and decision-making in sport, enhancing our scientific understanding of these phenomena and helping practitioners to develop interventions to facilitate the more rapid acquisition of the perceptual-cognitive skills that underpin these judgements. Adopting a multi-disciplinary approach--encompassing research from psychology, biomechanics, neuroscience, physiology, computing science and performance analysis--the book is divided into three primary sections. The first provides a comprehensive analysis of the processes and mechanisms underpinning anticipation and skilled perception in sport. The second's focus shifts towards exploring the science of decision-making in sport, while the final section's is more applied, outlining how the key skills that impact on anticipation and decision-making may be facilitated through various training interventions"--
Keywords: Sports / Psychological aspects / Research; Sports / Physiological aspects / Research; Decision making / Psychological aspects / Research; Sports sciences / Research; Neurosciences / Research; Physical education and training / Psychological aspects / Research